The Study of “Make Over” Advertisement on Instagram Caption: Persuasive Analysis - Sholikhatin, Sholikhatin (Journal of Literature, Linguistics, & Cultural Studies, 2023)
This study discusses the persuasive techniques used in advertising women's beauty products on Instagram social media. This study examines "Persuasive Analysis of Instagram Caption Ads "Make Over". The purpose of this research is to find out the types of persuasive techniques and strategies used in advertising beauty products on Instagram. techniques used in advertising beauty products from beauty product accounts. The source of the data in this study came from the captions of several beauty product accounts on "Make Over". The descriptive method was used to analyze the data using Keraf's theory (2004). The data was obtained from 16 captions on the "Make Over" beauty product. From the results of the study it was concluded that the most frequently used suggestion technique, from the 16 collected data sheets it can be seen that the persuasive presentation techniques used in advertising beauty products are: rationalization 38%, identification 13%, suggestions. 18%, 13% conformity, 6% compensation, 6% displacement, and 6% projection. Then, the techniques most often used in advertising are rationalization techniques and suggestion techniques because they are easier for advertisers to reach and attract consumers' attention. It is suggested to future researchers with the same topic to apply several other persuasive theories and not only focus on one theory for research improvement. Keywords: Persuasive technique, Advertisment Make Over.